Public Policies: School Feeding Program and Strengthening Family Agriculture : (Research, Society and Development, 2021)
The article verifies the performance of public policies: National School Feeding Program, the National Program for Strengthening Family Agriculture, to understand the organizational dynamics in the municipality of Brejo Santo/Ceará. To answer the research concerns, the study contemplates the survey of data, products and processes that involve the purchase of foodstuffs policies, for school meals, as well as the forms of production and commercialization. To achieve these objectives, a documental study was carried out, containing the analysis of the Minutes, Notices, with the executing units in the region, to diagnose the results of the programs, the production matrix, access to new markets, as well as the management of school meals. The research findings identified the strengthening of local associative organizations, the expansion of institutional relations, family involvement in production, in addition to care for the environment, pesticide-free production. It means special care with food safety, which indicates an improvement in the diet of families, as well as in the products on the school menu. This process has the presence of nutritionists, technical assistance in production, an organizational and institutional movement, capable of causing a new social and economic dynamic in the group of family farmers, who organize themselves into associations/cooperatives, to produce and market their products, provide better school nutrition.